Elementy teorii portfela w zarządzaniu należnościami - Michalski, Grzegorz (Operational Risk of the Buyers - Portfolio Management Approach in Accounts Receivables Management, 2007)
Wealth maximalization is the basic financial aim in management of an enterprise. Accounts receivables management must contribute to the realization of this aim. The article presents the method of determination accounts receivables in a firm based on portfolio management theory. Level of accounts receivables in a firm increases net working capital and costs of holding and managing accounts receivables. Both of them decrease value of the firm but liberal policy in accounts receivables with portfolio management approach could increase it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 260-273